IMPLEMENTASI STRATEGI PEMBELAJARAN BERDIFERENSIASI DALAM PENGAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Azminudin Latief; Sutama; Achmad Fathoni (STKIP Subang, 2024)
This study aims to analyze the implementation of differentiated Indonesian language learning in terms of process and content in grade V of SDN 01 Tunggulrejo, specifically focusing on the material of identifying the main idea of a paragraph. The research strategy used is a case study with a focus on planning, implementation, and evaluation of the differentiated learning process in Indonesian language instruction. Data sources include documents such as the annual program (Prota), semester program (Promes), syllabus, lesson plans (RPP), and student learning outcomes for grade V, as well as interviews with students, the class teacher, and the principal. Data collection techniques involve observation, document analysis, and interviews. Data were analyzed using Miles & Huberman’s interactive analysis, consisting of data reduction, data presentation, and conclusion drawing. The results show that lesson planning was carried out effectively through the systematic preparation of lesson plans (RPP) that include all essential components, including mapping student readiness. A scientific approach was applied to encourage students to be active, creative, and innovative. The implementation of differentiated learning involved grouping students based on their initial ability to understand the material. Each group received treatment tailored to their learning needs. Learning activities were designed to be engaging using images, videos, and ice-breaking activities to maintain student interest. Assessment was conducted comprehensively covering attitudes, knowledge, and skills, using various assessment tools such as observation, written tests, and performance sheets.